Multidimensional poverty and disability: A case control study in India, Cameroon, and Guatemala. (August 2020) - Pinilla-Roncancio, Mónica; Mactaggart, Islay; Kuper, Hannah; Dionicio, Carlos; Naber, Jonathan; Murthy, G.V.S.; Polack, Sarah
Abstract: Although the association between disability and multidimensional poverty has been consistently found in several studies in Low- and Middle-Income Countries. None of these studies so far has used an extended and internationally comparable questionnaire (extended Washington Group Questionnaire) and a clinical screening of disability. The purpose of this article is to calculate, compare and analyse the levels of multidimensional poverty of people with and without disabilities in Guatemala (national), in one district of Cameroon (Fundong Health District, North West Cameroon) and in one district in India (Mahbubnagar District, Telangana State). We used a case-control study approach; adults with disabilities identified in a population-based disability survey using the Washington Group Extended Questionnaire were matched to age-sex matched controls without disabilities and interviewed about their levels of access and use of different social services. Following the Alkire-Foster method, the levels of multidimensional poverty between cases and control were computed and compared. Additionally, we analysed how disability and other individual characteristics are associated with being poor in each country. The results showed that people with disabilities in all three-study settings face significantly higher levels of poverty and the intensity of their poverty is higher. In the case of Cameroon, differences in the levels of deprivation between people with and without disabilities were smaller than those observed in India and Guatemala. This might suggest that in countries with higher levels of human, economic and social development people with disabilities are being left behind by public policies aiming to reduce poverty and deprivation in basic indicators. In addition, indicators related to health contributed the most to the levels of multidimensional poverty for people with disabilities. These findings provide important evidence about the association of multidimensional poverty and disability and underline the importance of including indicators capturing individual deprivations to analyse poverty for this group. Highlights: Case control study analysing the levels of multidimensional poverty of people with and without disabilities in one province of India, Cameroon and in Guatemala. People with disabilities in the three countries have higher levels of multidimensional poverty and deprivation.